2022
DOI: 10.1186/s12985-022-01741-1
|View full text |Cite|
|
Sign up to set email alerts
|

Human papillomavirus genotype distribution in Ethiopia: an updated systematic review

Abstract: Background Cervical cancer is caused by infection with high-risk human papillomaviruses (HR-HPVs). It is one of the leading causes of cancer-related deaths in Ethiopia and globally. To develop efficient vaccination and HPV-based cervical cancer screening approaches, data on genotype distribution of HPVs is crucial. Hence, the study was aimed to review HPV genotype distribution in Ethiopia. Methods Research articles were systematically searched usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Globally, HPV18 is the most frequently detected HR-HPV next to HPV16 from advanced cervical lesions including cancer [18]. However, it was rare in our study and we reported a similar result in a recently published systematic review [19]. The reason behind the low involvement of HPV18 in cancer and high-grade cervical lesions in Ethiopia requires further studies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Globally, HPV18 is the most frequently detected HR-HPV next to HPV16 from advanced cervical lesions including cancer [18]. However, it was rare in our study and we reported a similar result in a recently published systematic review [19]. The reason behind the low involvement of HPV18 in cancer and high-grade cervical lesions in Ethiopia requires further studies.…”
Section: Discussionsupporting
confidence: 77%
“…A study by Gebremeskel et al [31] that specifically included women from the northern part of the country, reported the proportion of HR-HPVs among the identified HPVs to be 55.5%, which is almost the same as our finding. However, according to our recent systematic review, the proportion of HR-HPV among women with different kinds of cervical abnormalities was 77.5% in Ethiopia [19]. The HR-HPV prevalence reported in other African countries was also diverse; in Togo 53.3% [51], and Zimbabwe 96% [52].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the ATHENA research conducted in 2015, the most common HPV type detected in a detailed examination according to age groups is HPV 16, and in order of frequency, HPV 52, HPV 31, HPV 18 are the most common types [22]. In a systematic study in which data between 2005 and 2019 were analyzed, the most frequently detected HPV types were HPV 16, HPV 52, HPV 35, HPV 18, and HPV 56 [23]. When the HPV types seen in this study are examined, the two most common types are HPV 16 at 13.6% and HPV 56 at 11.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In a modeled scenario where vaccinating boys (aged 9–14) or women aged ≥ 18 was considered, Drolet and colleagues found less cost-effectiveness 22 . Ethiopia started an HPV-vaccination program for girls aged 14 in late 2018 with Gardasil-4TM (HPV 6, 11, 16, 18) 39 . A systematic review of 10 Ethiopian studies, including 3633 women with different kinds of cervical abnormalities, identified HPV 16 (37.3%), 52 (6.8%), 35(4.8%), 18(4.4%)) to be the most prevalent genotypes 39 , which calls for vaccines with a broader scope as HPV 18 might be of lesser importance.…”
Section: Discussionmentioning
confidence: 99%